Enabling robust blue circularly polarized organic afterglow through self-confining isolated chiral chromophore - Mingjian Zeng; Weiguang Wang; Shuman Zhang; Zhisheng Gao; Yingmeng Yan; Yitong Liu; Yulong Qi; Xin Yan; Wei Zhao; Xin Zhang; Ningning Guo; Huanhuan Li; et al. (Nature Communications, 2024)
Abstract Creating circularly polarized organic afterglow system with elevated triplet energy levels, suppressed non-radiative transitions, and effective chirality, which are three critical prerequisites for achieving blue circularly polarized afterglow, has posed a formidable challenge. Herein, a straightforward approach is unveiled to attain blue circularly polarized afterglow materials by covalently self-confining isolated chiral chromophore within polymer matrix. The formation of robust hydrogen bonds within the polymer matrix confers a distinctly isolated and stabilized molecular state of chiral chromophores, endowing a blue emission band at 414 nm, lifetime of 3.0 s, and luminescent dissymmetry factor of ~ 10−2. Utilizing the synergistic afterglow and chirality energy transfer, full-color circularly polarized afterglow systems are endowed by doping colorful fluorescent molecules into designed blue polymers, empowering versatile applications. This work paves the way for the streamlined design of blue circularly polarized afterglow materials, expanding the horizons of circularly polarized afterglow materials into various domains.